Are you feeling better now, Mr. Schmitt? (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
Bertolt Brecht's epic theater was contextualized as modern theater. In this way, the question was asked: does Brecht's epic theater still dialogue with the present time? As a methodological path, Walter Benjamin's suggestion of returning to the past in a backward reading was adopted. When returning to the foundations of modern. Western theater, specifically the epic theater model, we found procedures that are still resonant for today's scene.
Keywords: modern theater; epic model; rupture